2014
DOI: 10.1111/ecpo.12039
|View full text |Cite
|
Sign up to set email alerts
|

Politicians and Preferences of the Voter Majority: Does Gender Matter?

Abstract: Does the gender of political representatives affect the extent to which they adhere to the voter majority's preferences? By matching individual male and female representatives' votes on legislative proposals with real referendum outcomes on the same issues, we obtain a direct measure of divergence. We find that female and male representatives adhere equally close to the majority's preferences if party affiliations are taken into account. This suggests that observed gender differences with respect to the nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
3
12
1
Order By: Relevance
“…This finding is in line with the results provided by Stadelmann et al. (). Based on data from Swiss referenda, those authors show that male and female representatives adhere equally strongly to the preferences of the majority of voters.…”
Section: Estimation Results: Baseline Specificationsupporting
confidence: 94%
See 1 more Smart Citation
“…This finding is in line with the results provided by Stadelmann et al. (). Based on data from Swiss referenda, those authors show that male and female representatives adhere equally strongly to the preferences of the majority of voters.…”
Section: Estimation Results: Baseline Specificationsupporting
confidence: 94%
“…For example, we do not find any differences between male and female leaders with regard to deficit spending. This finding is in line with the results provided by Stadelmann et al (2014). Based on data from Swiss referenda, those authors show that male and female representatives adhere equally strongly to the preferences of the majority of voters.…”
Section: Estimation Results: Baseline Specificationsupporting
confidence: 88%
“…While this has often been cited in support of citizen-candidate, the imperfect beliefs voting model shows how such results could be driven by the fact that now only candidates who can communicate perfectly with female voters are being nominated, while before candidates tended to be able to communicate more easily with men. Such an alternative result is consistent with Stadelmann, Portmann and Eichenberger (2014), which found that there was generally no difference between male and female politicians except on social and redistributive issues, which are the most likely to be clouded by differences between gendered language. In this way, the imperfect beliefs voting model offers many opportunities to add to the exploration of particularistic public goods provision.…”
supporting
confidence: 83%
“…Articles investigating the influence of candidates' personal valence indicate that if voters consider such aspects, politicians have a potential leeway in their decisions (see Groseclose, 2001;Adams et al, 2010;Padovano, 2013). Apart from pure electoral competition (see Downs, 1957aDowns, , 1957b, legislative choices and the behavior of politicians may be explained by other factors, such as gender (see Gagliarducci and Paserman, 2012;Stadelmann et al, 2014), having daughters (see Washington, 2008), links to civil service (see Braendle and Stutzer, 2010), education (see Ruske, 2015), and numerous other socioeconomic characteristics and preferences (see, e.g., Ågren et al, 2007;Padovano and Ricciutti, 2009;Freier and Thomasius, 2012;Okulicz-Kozaryn, 2014). Important contributions in political science and sociology turned their attention relatively early to the question of whether military service and know-how specific to the use of force affect the political willingness to support military action (see Huntington, 1957;Nordlinger, 1977).…”
Section: Related Literature and Theoretical Considerationsmentioning
confidence: 99%
“…By advancing a so-called initiative and collecting 100,000 signatures, citizens can demand a popular vote on their own proposals for a constitutional amendment. Referenda reflect revealed preferences for policies, because they permit constituents to rank them against the status quo (see Schneider et al, 1981;Frey, 1994;Portmann et al, 2012;Carey and Hix, 2013;Portmann, 2014) and they entail real policy outcomes and consequences. This is a distinctive feature of our data.…”
Section: Institutional Setting and Datamentioning
confidence: 99%